2013
DOI: 10.1186/1476-072x-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Using statistical methods and genotyping to detect tuberculosis outbreaks

Abstract: BackgroundEarly identification of outbreaks remains a key component in continuing to reduce the burden of infectious disease in the United States. Previous studies have applied statistical methods to detect unexpected cases of disease in space or time. The objectives of our study were to assess the ability and timeliness of three spatio-temporal methods to detect known outbreaks of tuberculosis.MethodsWe used routinely available molecular and surveillance data to retrospectively assess the effectiveness of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Studies reporting the application of the spatial methods in the early identification of TB outbreak were uncommon. Space-time TB studies using retrospective surveillance data in the USA found that the spatial scan statistic and other methods could effectively detect outbreaks months before local public authorities became aware of the problem [ 25 , 28 ]. However, as space-time clusters of TB can be due to either ongoing transmission or reactivation, characterising the drivers that resulted in the spatial clustering is essential.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting the application of the spatial methods in the early identification of TB outbreak were uncommon. Space-time TB studies using retrospective surveillance data in the USA found that the spatial scan statistic and other methods could effectively detect outbreaks months before local public authorities became aware of the problem [ 25 , 28 ]. However, as space-time clusters of TB can be due to either ongoing transmission or reactivation, characterising the drivers that resulted in the spatial clustering is essential.…”
Section: Resultsmentioning
confidence: 99%
“…Clusters were eligible for random sampling selection if the cluster consisted of at least three TB patients residing in the same given public health jurisdiction, whose TB status were reported between January 1, 2006 and the time of cluster evaluation. Eligible clusters for each of the four sites (see above) were assigned to three priority groups (low, medium, and high priority) based on their calculated log-likelihood ratio (LLR: <1.00, 1.00-5.79, and ≥5.80, respectively) associated with the public health cluster priorities [ 20 , 21 ]. After reviewing the geospatial scores [ 21 ], initial expert panel rankings, and cluster investigation findings, the CDC statistician and the expert panel determined the log-likelihood ratio (LLR) cut-points that were associated with high-, medium-, and low-priority clusters in our surveillance data.…”
Section: Methodsmentioning
confidence: 99%
“…TB outbreaks among immigrants in the US were all associated with crowded environments and lack of access to medical care, whereas outbreaks involving mainly US-born persons were associated with substance abuse, homelessness and incarceration(250). A number of outbreaks with MDR strains have been described in foreign-born people in low prevalence countries(249,251,252).Statistical techniques, when applied retrospectively to routinely collected TB data, can successfully detect outbreaks, earlier than local public health authorities become aware of the problem(253). Routinely reported data may identify small clusters that are likely to become outbreaks and which are therefore candidates for intensified contact investigations.…”
mentioning
confidence: 99%